Ultra High Performance Concrete Reinforced with Short Steel and Carbon Fibers (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2015)
Fibers are usually used in High Performance Concrete with a purpose to increase bending strength and ductility. Important properties are the peak value of bearing stress (strength) and post-cracking behavior of bended element. In the framework of an experimental part, Ultra High Performance mix compositions were prepared using intensive mixer. Short steel fibers and carbon micro fibers in amount of 1% by volume, as well as its combination were used for cement matrix reinforcing. Results of compressive and bending tests proved an increase of strength value in the case of use both steel and carbon fibers. Carbon fibers were decreased the effect of explosive collapse of the UHPC cement matrix, at the same time still brittle bending behavior was take place. Steel fibers considerably improved bending ductility thanks to a pull-out mechanism of steel fibers. The best results were achieved in the case of combined application of both carbon and steel fibers.